Tropoelastin bridge region positions the cell-interactive C terminus and contributes to elastic fiber assembly - Yeo, Giselle C. (National Academy of Sciences, 2012)
The tropoelastin monomer undergoes stages of association by coacervation, deposition onto microfibrils, and cross-linking to form elastic fibers. Tropoelastin consists of an elastic N-terminal coil region and a cell-interactive C-terminal foot region linked together by a highly exposed bridge region. The bridge region is conveniently positioned to modulate elastic fiber assembly through association by coacervation and its proximity to dominant cross-linking domains. Tropoelastin constructs that either modify or remove the entire bridge and downstream regions were assessed for elastogenesis. These constructs focused on a single alanine substitution (R515A) and a truncation (M155n) at the highly conserved arginine 515 site that borders the bridge. Each form displayed less efficient coacervation, impaired hydrogel formation, and decreased dermal fibroblast attachment compared to wild-type tropoelastin. The R515A mutant protein additionally showed reduced elastic fiber formation upon addition to human retinal pigmented epithelium cells and dermal fibroblasts. The small-angle X-ray scattering nanostructure of the R515A mutant protein revealed greater conformational flexibility around the bridge and C-terminal regions. This increased flexibility of the R515A mutant suggests that the tropoelastin R515 residue stabilizes the structure of the bridge region, which is critical for elastic fiber assembly.